Long-term prognostic counselling in people with multiple sclerosis using an online analytical processing tool. (August 2021) - Kosch, Ricardo; Schiffmann, Insa; Daumer, Martin; Lederer, Christian; Scalfari, Antonio; Galea, Ian; Scheiderbauer, Jutta; Rahn, Anne; Heesen, Christoph
Background: Prognostic counselling is a sensitive issue in medicine and especially so in MS due to the highly heterogeneous disease course. However, people with MS (pwMS) seek prognostic information. The web-based 'Evidence-Based Decision Support Tool in Multiple Sclerosis' (EBDiMS) uses data of 717 patients from the London/Ontario cohort to calculate personalized long-term prognostic information. Objective: The aim of this study was to investigate the feasibility and effect of long-term prognostic counselling in pwMS using EBDiMS. Methods: Ninety consecutive pwMS were provided with personalized estimations of expected time to reach Expanded Disability Status Scale (EDSS) scores of 6 and 8 and time to conversion to secondary-progressive MS. Participants gave estimates on their own putative prognosis and rated the tool's acceptability on six-step Likert-type scales. Results: Participants rated EBDiMS as highly understandable, interesting and relevant for patient–physician encounters, coping and therapy decisions. Although it provoked a certain degree of worry in some participants, 95% would recommend using the tool. Participants' own prognosis estimates did not change significantly following EBDiMS. Conclusion: Long-term prognostic counselling using an online tool has been shown to be feasible in a clinical setting. EBDiMS provides pwMS with relevant, easy-to-understand, long-term prognostic information without causing relevant anxiety.